Effective dose of intranasal remimazolam for preoperative sedation in preschool children: a dose-finding study using Dixon’s up-and-down method - Ni, Ming-Jie; Jin, Yu-Ting; Wu, Qian-Lin; Zhang, Ning; Tian, Jia-He; Li, Jun; Yuan, Kai-Ming (Frontiers in Pharmacology, 2024)
Background: Most preschool children are distressed during anesthesia induction.While current pharmacological methods are useful, there is a need for further optimization to an "ideal" standard. Remimazolam is an ultra-short-acting benzodiazepine, and intranasal remimazolam for pre-induction sedation may be promising.Methods: This study included 32 preschool children who underwent short and minor surgery between October 2022 and January 2023. After pretreatment with lidocaine, remimazolam was administered to both nostrils using a mucosal atomizer device. The University of Michigan Sedation Score (UMSS) was assessed for sedation 6, 9, 12, 15, and 20 min after intranasal atomization. We used Dixon's up-and-down method, and probit and isotonic regressions to determine the 50% effective dose (ED50) and 95% effective dose (ED95) of intranasal remimazolam for pre-induction sedation.Results: Twenty-nine pediatric patients were included in the final analysis. The ED50 and ED95 of intranasal remimazolam for successful pre-induction sedation, when processed via probit analysis, were 0.65 (95% confidence interval [CI], 0.59-0.71) and 0.78 mg/kg (95% CI, 0.72-1.07), respectively. In contrast, when processed by isotonic regression, they were 0.65 (95% CI: 0.58-0.72 mg/kg) and 0.78 mg/kg (95% CI: 0.69-1.08 mg/kg), respectively. At 6 min after intranasal remimazolam treatment, 81.2% (13/16) of "positive" participants were successfully sedated with a UMSS ≧ 1. All the "positive" participants were successfully sedated within 9 min.Intranasal remimazolam is feasible for preschool children with a short onset time. For successful pre-induction sedation, the ED50 and ED95 of intranasal remimazolam were 0.65 and 0.78 mg/kg, respectively.